Trainers' Manual on Facilitating Local Government-Led Community-Driven Development : December 2018. (Asian Development Bank, 2018)
This publication documents the process and materials needed to conduct interventions supporting the transition to local government-led community-driven development in the Philippines. Under the technical assistance of the Asian Development Bank and financed by the Japan Fund for Poverty Reduction, it was developed in collaboration with the Department of Social Welfare and Development's National Program Management Office for its Kapit-Bisig Laban sa Kahirapan-Comprehensive and Integrated Delivery of Social Services National Community-Driven Development Program.